2021
DOI: 10.1016/j.ijedro.2021.100049
|View full text |Cite
|
Sign up to set email alerts
|

Practices and experiences of distant education during the COVID-19 pandemic: The perspectives of six- to sixteen-year-olds from three high-income countries

Abstract: The paper explores children's perspectives of distance education, their learning experiences and school satisfaction in Luxembourg, Germany and Switzerland during the first wave of the COVID-19 pandemic. The data stem from an online questionnaire completed by 1773 primary and secondary school children aged 6–16. While the paper uses quantitative and qualitative data, it aligns with the qualitative research tradition and predominantly uses an inductive approach. The findings show that teachers offered varied ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 28 publications
2
28
0
7
Order By: Relevance
“…Children's routines were disrupted with some parents and caregivers reporting sleep pattern disruptions, behavioural issues, and daily routines being disorganised and chaotic (Scarpellini et al, 2021;Segre et al, 2021). Evidence is emerging that Covid-19 restrictions also negatively impacted children's mental health and social connectedness specially for children with special needs (Sancho et al, 2021), while the overall daily life stress and pressure that parents and caregivers encountered increased (Araújo et al, 2021;Kirsch et al, 2021). Davis and Polatajko (2010) remind us as occupational therapists, "we need to be mindful of the nature of our clients' occupational repertoires and the personal, occupational and environmental situations that can hinder and/or enable it" (pp.…”
Section: Occupational Repertoires and Routinesmentioning
confidence: 99%
“…Children's routines were disrupted with some parents and caregivers reporting sleep pattern disruptions, behavioural issues, and daily routines being disorganised and chaotic (Scarpellini et al, 2021;Segre et al, 2021). Evidence is emerging that Covid-19 restrictions also negatively impacted children's mental health and social connectedness specially for children with special needs (Sancho et al, 2021), while the overall daily life stress and pressure that parents and caregivers encountered increased (Araújo et al, 2021;Kirsch et al, 2021). Davis and Polatajko (2010) remind us as occupational therapists, "we need to be mindful of the nature of our clients' occupational repertoires and the personal, occupational and environmental situations that can hinder and/or enable it" (pp.…”
Section: Occupational Repertoires and Routinesmentioning
confidence: 99%
“…Significant obstacles caused by the pandemic identified key areas that require urgent actions in the educational sector. In particular, the appropriate implementation of educational work in this period requires the availability of additional electronic devices and a stable connection to the World Wide Web (Kirsch, Engel de Abreu, Neumann, Wealer, 2021). In addition, educators need to have ICT competencies, be ready to work online, set and test educational tasks, and organize effective communication with students (Bonal, González, 2020).…”
Section: Challenges In the Education System Duementioning
confidence: 99%
“…The physical and psychological transition to home-based learning also created an opportunity to see how institutional schools provide much more than just a location for learning. Instead, they provide a multitude of social programs and physical accommodations to the community (Dwyer, 2022;Kirsch et al, 2021).…”
Section: Disability Studies and Social Constructionist Theorymentioning
confidence: 99%
“…Schooling resources were difficult to access and there was an overall lack of communication between the institutional school systems, teachers, and the families (Bartlett & Schugurensky, 2020;Fontenelle-Tereshchuk, 2020;Lee et al, 2020). It was also found that many children could not focus or did not know how to structure their studies in a way that was helpful for learning (Fontenelle-Tereshchuk, 2020;Kirsch et al, 2021). In contrast, there were also multiple cases where children excelled in the home environment and some children enjoyed "that they could organize their work autonomously and work independently" (Kirsch et al, 2021, p. 8).…”
Section: Home-based Learningmentioning
confidence: 99%